The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13173887
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hydrogen Diffusion Behavior during Welding of Heavy Plate

Abstract: For the multi-layer and multi-pass welding process of the heavy plate, the hydrogen diffusion behavior was numerically simulated to study the effect of solid-state phase transition (SSPT) on the hydrogen diffusion in the thickness direction, and the influence of the residual stress-induced diffusion after SSPT. The calculation results were compared with the experimental results. The comparison shows that the distribution of hydrogen concentration in the direction of thickness was in good agreement. The positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…Due to the large plate thickness, long diffusion times have to be anticipated independently of the used diffusion coefficients. Nonetheless, the obtained differences in the diffusion coefficients (see 34). From the viewpoint of any HAC concern, it has to anticipated that our simulation shows the normalized hydrogen concentration, i.e., it can be multiplied with any value as initial concentration.…”
Section: Numerical Analysis Of Hydrogen Diffusion In the Weldedmentioning
confidence: 88%
“…Due to the large plate thickness, long diffusion times have to be anticipated independently of the used diffusion coefficients. Nonetheless, the obtained differences in the diffusion coefficients (see 34). From the viewpoint of any HAC concern, it has to anticipated that our simulation shows the normalized hydrogen concentration, i.e., it can be multiplied with any value as initial concentration.…”
Section: Numerical Analysis Of Hydrogen Diffusion In the Weldedmentioning
confidence: 88%
“…A hegesztés következtében fellépő hidegrepedést általában a hegesztett kötésben három együttesen fellépő tényező okozza: a kemény szövetszerkezet (mint például a bénit vagy martenzit), a diffúzióképes hidrogén jelenléte és a magas (maradó) feszültségállapot (2. ábra). A hegesztett kötés kialakítása közben, különösképpen, ha nagyszilárdságú acélról van szó, az előbb említett három tényező az idő változásával összetett módon változik és egymást is befolyásolja [6,11,[16][17][18].…”
Section: Hidegrepedés a Hegesztett Kötésekbenunclassified
“…The results showed that the concentration of hydrogen ions at the crack tip is higher due to the effect of residual stress in the material, and the residual tensile stress could enhance hydrogen diffusion and concentration. Yang et al [28] investigated the phenomenon of hydrogen diffusion induced by the changes of residual stress from solid-state phase transition in thick rigid plate welding. Sato et al [29] analyzed the correlation between cold cracking, surface residual stress and hydrogen aggregation within the high-strength steel weld bead.…”
Section: Introductionmentioning
confidence: 99%